Noncommutative Phase Space Schrödinger Equation with Minimal Length - H. Hassanabadi; Z. Molaee; S. Zarrinkamar (Advances in High Energy Physics)
We consider the Schrödinger equation under an external magnetic field in two-dimensional noncommutative phase space with an explicit minimal length relation. The eigenfunctions are reported in terms of the Jacobi polynomials, and the explicit form of energy eigenvalues is reported.